Coronal microleakage of Enterococcus Faecalis in three types of endodontic filling (warm vertical compaction, lateral compaction, and single cone) - Rendón-Gómez, Jaime Alberto; Bermúdez-Reyes, Patricia; Cano-Pérez, José Daniel; Urrego-Araque, Miguel Ángel (Revista Facultad de Odontología Universidad de Antioquia, 2017)
Introduction: the adequate sealing of endodontic fillings is critical for a successful treatment, as it prevents the entry of microorganisms and/or their growth in case they persist within the root system. The purpose of this study was to determine bacterial microleakage time in root canals filled with the lateral compaction, warm vertical compaction, and single cone techniques. Methods: 30 single-rooted teeth extracted from humans were randomly distributed into three experimental groups (n = 8); positive and negative controls were also used (n = 6). Teeth were prepared with the corono-apical ProTaper Universal technique and obturations were performed using lateral compaction, warm vertical compaction (System B – Obtura II) and single cone. Top Seal resin-based cement was used in the three groups. Enterococcus faecalis (E. faecalis) microleakage was assessed every 24 hours for 30 days using the dual chamber model, with the lower chamber containing a pH indicator in the culture medium, which showed bacterial microleakage time. The data were statistically analyzed using one-way Anova test and Bonferroni and Tukey’s post-tests. Results: The single-cone technique showed the highest level of bacterial microleakage of E. faecalis as a function of time, while lateral compaction and warm vertical compaction showed better results, with no statistically significant differences between them, being the techniques with the best sealing results against E. faecalis microleakage. Conclusions: Under the conditions of this study, it can be concluded that the single-cone technique is not suitable for root canal sealing, as it does not prevent bacterial microleakage of E. faecalis compared to the other two techniques.